Forced motion control of a mobile robot - T. Yu. Kim; R. A. Prakapovich; A. A. Lobatiy (Informatika)
Objectives. The increase of the efficiency of a separate transport mobile robot in a warehouse due to optimal regulation of the speed of its movement. It is required to control the position, speed, acceleration and direction of movement of the mobile robot at each moment of time along a known route. A method for forced control of the movement of a transport mobile robot was proposed. A control block for various motion maneuvers was developed in Simulink environment, which calculates the distance to the nearest turning point or stop and then by constructed cyclogram the corresponding speed at each moment of time is determined. The proposed control unit can be used in practice for the tasks of optimal movement of transport robots in predetermined area.Methods. The method of the theory of optimal control according to the criterion of maximum speed, the wave algorithm for finding the shortest path, the method of finite automata for relay control of the acceleration of movement are used.Results. Based on the proposed method of forced control of the movement of a transport mobile robot in the Simulink environment, a maneuver control system was developed that provides the minimum travel time for each segment of the path. Maneuvers mean the rectilinear movement of the robot, as well as its turn on the spot, in two modes: with and without reaching maximum speed. The technique is based on the assumption that the movement of the transport robot is uniformly accelerated. A side result of the developed control system is that when it is scaled to a group of robots, it becomes possible to predict the time and place of their potential collisions, in order to subsequently take into account a group of robots for effective control.Conclusion. The developed control system can be used to control a real transport mobile robot equipped with a servo drive in solving the problems of transporting goods around the warehouse.